Concerns and the Seriousness of Emotion. (7th November 2017) - Monteleone, John M.
Abstract: Some philosophers have claimed that emotions are states of mind where an object is taken seriously. Seriousness, as this paper understands it, involves both a phenomenological change in attention and non‐indifference towards an object. The paper investigates how contemporary theories of emotion can explain the seriousness of emotion. After rejecting explanations based on feeling, desire, and concern, the paper argues that the seriousness of an emotion can be explained as the manifestation of a concern in an outwardly directed feeling. Given the lack of competing explanations, seriousness probably must be explained this way. This argument shows how emotional feelings constitutively depend on desires, and why desires are essential ingredients to emotion.